The productive skill of requesting in children with Down syndrome: A case study - Yahya Gordani; Mahnaz Ezhdehakosh (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
The present case study aimed to investigate the nature of making requests by a child with Down Syndrome (DS) who has never received any medical intervention. To this aim, more than 180 hours of observation of a four-year-old male case in the field, together with interviews of parents and a relative, were analyzed qualitatively. Findings demonstrated a strong enthusiasm by the DS child to get involved in social communication. Although the DS child did not clearly understand the context of communication in terms of the rules for manner (mainly politeness and face), and he also lacked a sound understanding of the social functions to negotiate the meaning, he could differentiate among different settings in which there is need for a range of communication degrees. With mental and physiological issues contributing to problems with language production, the case had developed a limited repertoire, including voices, some fixed words or expressions, and mostly gestures to help him make requests. On the other hand, the child demonstrated good receptive skills; he could perceive the illocutionary force behind requests. However, if the sentence got a bit complicated in terms of pragmatics, he would become confused and prefer to stay silent rather than trying to insist on another response. It is hoped that by providing a good education for these children in a place where they are socially welcomed, they can forge useful relationships with their peers and take positive actions to become socially mature and be good community members.